PENERAPAN MODEL PEMBELAJARAN PBL BERBANTUAN MEDIA KONKRET UNTUK MENINGKATKAN KEMAMPUAN MENYELESAIKAN SOAL CERITA MATEMATIKA KELAS II - Hasti Fiyandari, Eva; Nirwansyah, Anang Widhi; Mulyati, Yuni (Journal of Professional Elementary Education, 2024)
The application of the probing prompting learning model to students' critical thinking skills in science subjects. A quasi-experimental study with a non-equivalent control group design. The research was conducted at SD Negeri Sumur Peuteuy. The sampling technique used was purposive sampling. In this study, class IV A was used as the experimental class and class IV B as the control class. This study aims to determine whether there are differences in students' critical thinking skills using the probing prompting learning model and students using the direct learning model. The purpose of the data analysis technique is to test the hypothesis using two tests and the right-hand side test. Based on the two-party hypothesis, tcount = 4,599 and ttable 2,010 so 4,599 > 2,010, meaning Ho is rejected and Ha is accepted. From this research, it can be said that the learning model applied in the experimental class (probing prompting learning model) and in the control class (direct learning model) shows the students' critical thinking skills. And the experimental class is better than the control class. This research aims to improve the ability to solve mathematics story problems in class II students at Kedungmalang Elementary School through a problem based learning (PBL) learning model assisted by concrete media. Learning using the Problem Based Learning model assisted by concrete media can improve students' ability to solve math story problems. This research method uses a type of classroom action research. The subjects of this research were all class II students at SD N Kedungmalang. Data collection techniques use tests, non-tests, observation and documentation. The results of this research can be proven by the average score obtained by students in the first cycle fraction material which was 73.63 with a percentage of 65% with the criteria not having reached the specified criteria. Cycle II got an average score of 81.59 with a percentage of 85% with the criteria having reached the specified criteria